Intramolecular photo‐driven electron transfer in the series of DMABN related compounds with para‐substituted acceptors. Study of the rate constants by Marcus theory. (15th December 2019) - Volchkov, Valery V.; Khimich, Mikhail N.; Rusalov, Mikhail V.; Gostev, Fedor E.; Shelaev, Ivan V.; Nadtochenko, Viktor A.; Gromov, Sergey P.; Melnikov, Mikhail Ya.
Abstract: A series of DMABN‐related compounds with two‐band fluorescence was studied by steady‐state absorption and fluorescence spectroscopy, time‐resolved absorption spectroscopy upon excitation with a 30‐fs laser pulse, and by TDDFT and xMCQDPT2 quantum chemical methods. The efficiency of the intramolecular electron transfer was found to depend on the excitation wavelength in MeCN. The reaction is described by a two‐state scheme (LE↔CT); the Stevens‐Ban method gives underestimated values for the reaction enthalpy Δ H ( SB ). The spectral luminescence and kinetic parameters, rate constants, and barriers for the forward ( k 1, E a ) and reverse ( k −1, E d ) electron transfer were calculated. The Marcus plot for k 1 versus the driving force (−Δ G ) and the total reorganization energy ( λ ) were calculated for six compounds. It was shown that without a barrier, the 1/ k 1 value (267 fs) is close to the mean solvation time in MeCN (260 fs), ie, the reaction rate is completely determined by the solvent. The results of conformational analysis for all studied compounds are consistent with the twisted intramolecular charge transfer model of structural relaxation. Abstract : A series of DMABN‐related compounds with two‐band fluorescence was studied by steady‐state absorption and fluorescence spectroscopy, time‐resolved absorption spectroscopy, and by TDDFT and xMCQDPT2 quantum chemical methods. The spectral luminescence and kinetic parameters, rate constants, and barriers for the forward (k1, Ea ) and reverse (k−1, Ed ) electron transfer were calculated. It was shown that without a barrier, the 1/k1 value (267 fs) is close to the mean solvation time in MeCN (260 fs), ie, the reaction rate is completely determined by the solvent.